Secondary Metabolites of The Fabaceae Plant Family A Review of Extraction Methods, Molecules and Bioactivity - Sowe, Momodou Salieu; Etonihu, Anayo Christian; Tarigan, Indra Lasmana; Muadifah, Afidatul (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2025)
Traditional medicine helps manage and treat various illnesses worldwide, particularly in Africa and Asia. For example, Traditional Indonesian Medicine (Jamu), Traditional Indian Medicine (Ayurveda), and Traditional African Medicine use a range of indigenous herbs to treat health conditions like fevers, malaria, diarrhea, diabetes mellitus, Asthma, and hypertension. Alkaloids, flavonoids, saponins, terpenoids, and polyphenols are bioactive substances with anti-inflammatory, antibacterial, and antioxidant effects in plants. The Fabaceae family consists of flowering plants, peas, legumes, woody trees, and shrubs. Fabaceae plants are widely used across Africa and Asia for traditional medicinal purposes. In addition, Fabaceae plants have significant economic value as a source of wood for the timber industry. This review highlights extraction methods, isolated molecules, and antimicrobial and antioxidant activity of Fabaceae plants found in Africa and Asia. We also detailed secondary metabolite molecules extracted from Fabaceae plant body parts and their identified bioactivities. This review compiles scientific information on the phytochemicals and pharmacological properties of plants in the Fabaceae family that could be useful for future drug candidate investigations.